2005
DOI: 10.1016/j.ydbio.2005.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The lesswright mutation activates Rel-related proteins, leading to overproduction of larval hemocytes in Drosophila melanogaster

Abstract: The lesswright (lwr) gene encodes an enzyme that conjugates a small ubiquitin-related modifier (SUMO). Since the conjugation of SUMO occurs in many different proteins, a variety of cellular processes probably require lwr function. Here, we demonstrate that lwr function regulates the production of blood cells (hemocytes) in Drosophila larvae. lwr mutant larvae develop many melanotic tumors in the hemolymph at the third instar stage. The formation of melanotic tumors is due to a large number of circulating hemoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 66 publications
6
65
1
Order By: Relevance
“…We analysed the expression pattern of these in the PGs of lwr homozygous mutants that had reached L3 (Chiu et al, 2005;Huang et al, 2005a). Similar to smt3i, in lwr mutant larvae we detected severe alterations in the expression levels of Dib (not shown) and βFtz-f1 (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…We analysed the expression pattern of these in the PGs of lwr homozygous mutants that had reached L3 (Chiu et al, 2005;Huang et al, 2005a). Similar to smt3i, in lwr mutant larvae we detected severe alterations in the expression levels of Dib (not shown) and βFtz-f1 (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…The formation of melanotic tumors has also been observed in lwr mutant larvae (Chiu et al, 2005;Huang et al, 2005) ), increased lamellocyte differentiation was observed without an increase in the total number of circulating hemocytes (Chiu et al, 2005). Melanotic tumor formation could still take place in these animals but with lower penetrance.…”
Section: N1mentioning
confidence: 90%
“…This phenotype suggests that cactus and dorsal are expressed in some tissues that do not express Toll (Minakhina and Steward, in press). Studies of the lesswright gene, which encodes a small ubiquitin-like modifier (SUMO)-adding enzyme, indicate that SUMO addition is required for proper regulation of Dorsal and Dif in hemocytes: namely, loss-of-function lesswright mutations result in constitutively nuclear Dorsal and Dif proteins in hemocytes and the formation of melanotic tumors owing to increased numbers of hemocytes (Huang et al, 2005). Similarly, the Drosophila Ubc9 SUMO-lating gene also appears to repress Dorsal and Dif function in controlling lamelocyte proliferation and drosomycin gene expression (Chiu et al, 2005).…”
Section: Additional Functions Of Drosophila Nf-kb Proteinsmentioning
confidence: 99%